Խ. Աբովեանն ու նրա ստեղծագործութիւնները՝ Արշակ Չօպանեանի հայեացքով - Բալայեան, Նաիրա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статьи Аршака Чопаняна, написанные к 50-летию со дня исчезновения Х. Абовяна и 100-летию со дня его рождения стали исследовательской основой данной статьи. В статье рассматриваются важнейшие мысли концепции Чо- паняна-литературоведа-исследователя, в связи изложением с определенными принципами биографию Абовяна, основоположника новой армянской литературы, и определением основных способов анализа его известных и неизвестных произведений. В статье представлены, рассматриваются, сравниваются и анализируются точки зрения Чопаняна на роман «Рана Армении», связанные с характером Агаси, типом армян, который борется или подчиняется, истокам патриотического скорби, политическим направлением в контексте поиска спасения армянского народа, сближение отношений с российским правительством и опора на его помощь. Эти статьи Чопаняна, отличающиеся нелинейными, примечательными, а порой и глубокими аспектами в абовянских исследованиях и сегодня сохраняют свою актуальность и нуждаются в постоянном освещении. Arshag Chobanian’s articles, written on the 50th anniversary of Kh. Abovyan’s disappearance and the 100th anniversary of his birth became the research basis of this article. The article discusses the most important thoughts of Chobanian’s concept of literary scholar-researcher, in connection with the presentation of the biography of Abovyan, the founder of the new Armenian literature, with certain principles, and determining the main ways of analyzing his known and unknown works. The article presents, examines, compares and analyzes Chobanian’s views on the novel “The Wound of Armenia” particularly focusing on Aghasi’s character, the dichotomy of Armenians who fight or submit, the origins of patriotic grief, the political trajectory concerning the Armenian people’s salvation quest, the rapprochement with the Russian government and reliance on its help. These articles by Chobanian, characterized by their non-linear, noteworthy, and sometimes profound aspects in studies on Abovyan, are still relevant today and need constant coverage by scholars.
Keywords: Բանասիրութիւն